2007
DOI: 10.1007/s00259-007-0600-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SSS and SRS calculated from normal databases provided by QPS and 4D-MSPECT manufacturers and from identical institutional normals

Abstract: Considerable differences between SSS/SRS obtained with QPS and 4D-MSPECT were found when using M-NDB. Even using identical patients and identical I-NDB, the algorithms still gave substantial different results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Knollmann et al13 compared summed scores using the manufacturer-based and institution-based normal database. Both QPS and 4D-MSPECT yielded higher scores when the institutional database was used as opposed to the manufacturer’s database, but the authors did not compare the characteristics and differences between the databases.…”
Section: Discussionmentioning
confidence: 99%
“…Knollmann et al13 compared summed scores using the manufacturer-based and institution-based normal database. Both QPS and 4D-MSPECT yielded higher scores when the institutional database was used as opposed to the manufacturer’s database, but the authors did not compare the characteristics and differences between the databases.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing manufacturer databases and institutional databases, Knollmann et al found some differences in quantitative scores between software algorithms as well as between manufacturer databases [9]. The merit of an individualized database is its specificity to camera types, camera rotation ranges, orbits, multi-detector configuration, and therefore higher diagnostic performance would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Validated automated algorithms provide semi-quantitative assessment of myocardial perfusion and left ventricular systolic function 11. In this study we aimed to assess the correlation between homocysteine level and myocardial SPECT abnormalities in 120 patients with suspected myocardial ischaemia.…”
Section: Introductionmentioning
confidence: 99%